2012
DOI: 10.1097/pcc.0b013e3182192c66
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mechanical ventilation time before initiation of extracorporeal life support on survival in pediatric respiratory failure

Abstract: There was a clear relationship between the number of mechanical ventilation days before the initiation of extracorporeal life support and survival. However; there was no statistically significant decrease in survival until >14 days of pre-extracorporeal life support ventilation was reached regardless of underlying diagnosis. We found no evidence to suggest that prolonged mechanical ventilation should be considered as a contraindication to extracorporeal life support in children with respiratory failure before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Type III phosphodiesterase inhibitors (amrinone, milrinone, enoximone) and the calcium sensitizer levosimendan can be helpful because they overcome receptor desensitization. Forty-one percent of children with a diagnosis of sepsis requiring ECMO for respiratory failure survive to hospital discharge (573). In two RCTs, pentoxifylline reduced mortality from severe sepsis in newborns (510,(560)(561)(562)(563)(564)(565)(566)(567)(568)(569) Rationale.…”
Section: We Suggest That Patients With Low Cardiac Output and Elevatedmentioning
confidence: 99%
“…Type III phosphodiesterase inhibitors (amrinone, milrinone, enoximone) and the calcium sensitizer levosimendan can be helpful because they overcome receptor desensitization. Forty-one percent of children with a diagnosis of sepsis requiring ECMO for respiratory failure survive to hospital discharge (573). In two RCTs, pentoxifylline reduced mortality from severe sepsis in newborns (510,(560)(561)(562)(563)(564)(565)(566)(567)(568)(569) Rationale.…”
Section: We Suggest That Patients With Low Cardiac Output and Elevatedmentioning
confidence: 99%
“…In previous reports, the mortality was higher if ECMO was started after 7 days of high‐level ventilation . This was not found here or in the ELSO registry for children . Therefore, prolonged mechanical ventilation should not be considered as a contraindication.…”
Section: Discussionmentioning
confidence: 54%
“…To this end, prior studies have reported an association between longer duration of pre-ECMO mechanical ventilation and poor patient survival [911]. Of note, the majority of respondents in the current study did not consider the duration of mechanical ventilation during an index hospitalization an important trigger for transfer and felt other considerations such as illness severity, the presence of ARDS, and suitability for ECMO were more germane to the decision making than the duration of mechanical ventilation solely.…”
Section: Discussionmentioning
confidence: 99%